Pemerolehan Bahasa Jepang bagi Siswa Sekolah Dasar melalui Pemanfaatan Desain Buku Yasashii Nihongo - Isnin Ainie; Suhartawan Budianto; Desy Irmayanti (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang, 2025)
The acquisition of foreign languages from an early age holds great potential, as children possess a natural ability to absorb language contextually and intuitively. In this regard, textbooks become one of the crucial elements supporting successful learning. This study explores the use of the Yasashii Nihongo textbook design in the process of Japanese language acquisition among elementary school students, based on the perspective of native speakers. Yasashii Nihongo is a Japanese language textbook designed interactively through a sociocultural approach that emphasizes the daily life context of children in Japan while being adapted to Indonesian culture. The research method used is descriptive qualitative. Data collection techniques include observation, questionnaires, and interviews. The research findings show that the design of the Yasashii Nihongo textbook has significant potential to assist elementary school students in acquiring the Japanese language. This is because the design of Yasashii Nihongo 1) has a highly organized structure; 2) uses simple yet clear language; 3) provides highly relevant content to daily life; 4) utilizes effective and appealing illustrations; 5) offers sufficient exercises and evaluations; 6) aligns with the developmental stages of elementary school students; and 7) provides accurate reference information along with sociocultural insights into Japanese life that are relevant to the students' daily experiences